2018
DOI: 10.1002/chem.201803833
|View full text |Cite
|
Sign up to set email alerts
|

Autopoietic Behavior of Dynamic Covalent Amphiphiles

Abstract: The condensation of aldehydes and amines in water to give amphiphilic imines can lead to a particular autocatalytic behavior known as autopoiesis, in which the closed micellar structure made by the amphiphile at the mesoscale can accelerate the condensation of its constituents. Herein, through a combination of analytical tools, including diffusion ordered spectroscopy (DOSY) as well as light, neutron, and X-ray scattering techniques, the thermodynamic and kinetic parameters were probed at both the level of dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
(88 reference statements)
0
6
0
Order By: Relevance
“…At this moment, the concentration of imine is 5 mM, and the increase in size corresponds to the entrapment of the released hydrophobic aldehyde in the remaining micellar imine structures, as described in our previous studies. [46,48,49] In addition, after 3 h, another population of larger objects (R h > 100 nm) appeared with a rapidly increasing size of 0.65 nm min À 1 , and this microemulsion continued to grow after the disappearance of the small micelle population, leading to a turbid solution and eventually to a macroscopic phase separation (Figure 4c). From these preliminary results using our reference imine A2, we tried to explore the possibility of stabilizing the micellar structure by introducing hydrogen bonding units into the imine surfactants.…”
Section: General Stability Rules Of Amphiphilic Imines In Watermentioning
confidence: 99%
See 2 more Smart Citations
“…At this moment, the concentration of imine is 5 mM, and the increase in size corresponds to the entrapment of the released hydrophobic aldehyde in the remaining micellar imine structures, as described in our previous studies. [46,48,49] In addition, after 3 h, another population of larger objects (R h > 100 nm) appeared with a rapidly increasing size of 0.65 nm min À 1 , and this microemulsion continued to grow after the disappearance of the small micelle population, leading to a turbid solution and eventually to a macroscopic phase separation (Figure 4c). From these preliminary results using our reference imine A2, we tried to explore the possibility of stabilizing the micellar structure by introducing hydrogen bonding units into the imine surfactants.…”
Section: General Stability Rules Of Amphiphilic Imines In Watermentioning
confidence: 99%
“…Such supramolecular structures can affect the stability of the imine bond by protecting it from water when it is integrated in the hydrophobic micellar core. [49] 1 H NMR spectra and by plotting the imine concentration as a function of time following Equation (1):…”
Section: General Stability Rules Of Amphiphilic Imines In Watermentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, we have built dynamic imines connecting hydrophobic and hydrophilic moieties in order to generate dynamic covalent amphiphiles, which can protect their imine bonds from fast hydrolysis in water because of their self-assembly in various micellar structures. [14][15][16] In particular, in the preceding paper, [17] we showed that amphiphilic imines (e. g. 1-4, Scheme 1), obtained by condensation of a fragrance aldehyde as the hydrophobic part with an amine derived from a poly(propylene oxide) and poly(ethylene oxide) diblock copolymer of variable length (such as Jeffamines® M1000 and M2070) as the hydrophilic section have surfactant properties and self-assemble into micellar structures in water. We furthermore demonstrated that placing the hydrolytically labile imine group within the hydrophobic part of the micelle, for example by using a linker between the labile imine group and the hydrophilic part of the amphiphile, resulted in relatively stable structures.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers addressed this puzzling issue, without a true, encouraging success, yet. Maturana's pioneering work on the concept of "autopoiesis" [21][22][23], which can be retrieved in very recent papers [22][23][24][25], introduced intriguing insights about how life is "auto-representing". Maturana, however, stands on a plain philosophical ground.…”
Section: Introductionmentioning
confidence: 99%